Combined remediation effects of biochar, zeolite and humus on Cd-contaminated weakly alkaline soils in wheat farmland. (September 2022) - Wang, Weihua; Lu, Tao; Liu, Lihu; Yang, Xiong; Li, Xuanzhen; Qiu, Guohong
Abstract: Threats posed by Cd-contaminated arable soils to food security have attracted increasing attention. The combination of organic and inorganic amendments has been extensively applied to immobilize Cd in paddy soils. However, the regulatory mechanism of Cd fractionation under these combined amendments and the effect on wheat Cd accumulation remain unclear in upland soils. In this work, different combinations of organic and inorganic amendments were prepared with biochar, zeolite and humus, and the Cd-immobilization mechanism was also investigated in field experiments. The results demonstrated that the mixture of biochar, zeolite and humus had excellent Cd immobilization performance in highly Cd-contaminated (4.26 ± 1.25 mg kg −1 ) weakly alkaline soils, resulting in 76.5–84.8% decreases in soil available Cd. The contribution of single components to Cd immobilization in the combined amendment follows the order of humus > biochar > zeolite. The combined amendment converted the acid soluble Cd to the Cd bound to the reducible fraction with higher stability, thereby decreasing Cd bioavailability. The maximum Cd decrease rate in wheat roots, straw and grains could reach 68.2%, 45.0% and 59.3%, respectively, and the Cd content in grains (0.098 mg kg −1 ) was lower than the food security standards of China (0.1 mg kg −1 ). Wheat planting for two successive years in a large-scale field further verified the superior Cd immobilization performance and stability of the combined amendment in moderately to slightly Cd-contaminated soil. The present study provides references for the remediation of Cd-contaminated weakly alkaline upland soils and certain guidance for safe food production. Graphical abstract: Image 1 Highlights: Organic-inorganic combined amendment has excellent immobilization effect on soil Cd. Cd content in wheat grains was decreased to below the food security standard of China. The combined amendment converted acid soluble Cd to reducible Cd. The combined amendment showed high stability for Cd immobilization.